The effect of core training on dynamic balance and strength endurance in junior field hockey players - Ramasamy, S.; Franklin, J.; Govindhara, P.; Panneerselvam, S. (Baltic Journal of Health and Physical Activity, 2022)
Introduction: The objective of this study is to find the effectiveness of core muscle strength training on dynamic balance and muscle endurance among junior field hockey players. Material and Methods: The study was conducted with 30 regular junior hockey players (15 in the control group and another 15 in the experimental group). The modified Star Excursion Balance Test (mSEBT) and Biering-Sorensen muscle endurance tests are used to assess dynamic balance and endurance. In the control group, the participants continued their formal training without undergoing any intervention. At the same time, the players in the experimental group performed the core muscle strength training daily for 45 minutes per session for eight weeks. Results: The result showed a statistically significant difference seen on both mSEBT and Biering Sorensen Endurance test between the control and experimental groups. The mSEBT had a higher mean score in the experimental group, right limb (97.6%) and left limb (97.9%), than the control group right limb (91.7%) and left limb (92.6%). The mean endurance time in the experimental group had a higher endurance time of (135.4 sec) than the control group (176.2 sec). Conclusion: This study showed that core muscle strengthening exercises enhance the dynamic balance and endurance in junior field hockey players.